Demographics, facilitators, and barriers among predominantly heated yoga users: a survey of the largest U.S. yoga studio brand - Nyer, Maren; Montinola, Sofia; Pegg, Samantha; Alsaadi, Yousif; Soetan, Zainab O.; Foster, Simmie; Rabideau, Dustin J.; Peacock, Juliana; Wu, Yian; Kinnas, Anna; Mischoulon, David; Sylvia, Louisa G. (Frontiers in Psychology, 2025)
The present study surveyed predominantly heated yoga users (N = 2,514) from CorePower Yoga, the largest U.S. yoga studio brand, to explore: (1) demographic characteristics and (2) facilitators and barriers to class participation. The sample was predominantly white (78%), at least 4-year college educated (90%), and female (87%). Twenty-three percent of participants (n = 587) self-reported being diagnosed with clinical depression. Most participants practiced yoga several days a week, and for at least 2 years, predominantly heated yoga classes. Out of a list of options, participants selected facilitators to heated yoga practice and barriers to yoga practice. Physical and mental health benefits of heated yoga facilitated their practice, whereas being around others, improved sleep, and reduction of physical pain were ranked as the lowest facilitators. Scheduling and expense related concerns were the highest ranked barriers to yoga classes, while not liking class participants, administrative issues, and discomfort with exercising around others were the lowest ranked barriers. Overall, these barriers and facilitators were generally consistent across subgroups (e.g., age, gender, race, ethnicity). Participants with self-reported diagnosed clinical depression reported improvement in mood as a more important facilitator than improvement in physical health, and barriers were consistent with the general survey population. Further research is needed to characterize facilitators and barriers to practice and strategies for improved usage.